ANALISIS KEMAMPUAN SISWA SMP DI KOTA PALU DALAM MEMECAHKAN MASALAH SEGIEMPAT BERDASARKAN GAYA KOGNITIF - Athira, Andi Mirna (JSTT, 2015)
The purpose of this study were: (1) To describe the capability of SMP student’s field dependent cognitive style in solving quadrilateral problem, (2) To describe the capability of SMP school student’s field independent cognitive style in solving the quadrilateral problem. This study is an exploratory study by qualitative descriptive approach. Subjects of this study were 2 students of IX SMP AL-Azhar. Data collection techniques by cognitive style test, mathematics test, and interview.Cognitive style test was used to retrieve data about cognitive style, a math test was used to determine the student's capability to solve quadrilateral problems, and while the interview technique used was unstructured interviews, to determine matters relating to student answers. The data analysis techniques used are reduce the data, presentation of data, triangulation of data, and drawing conclusions. Based on the data analysis results, it can be concluded that: (1) Subjects haveFIcognitivestylesfaster to under stand the problem, compared with students have FD cognitive style of FD. Subjects with FD cognitive styles hould read 4 times and even more tounder stand the given problem. Different from subjects with FI cognitive styles who just byread 2 times, able to understand the given problem. (2) Subjects with FI cognitive style makes 2 alternative complete problem solving plans, and able to use the formula of plane area related by given problems, while subjects with FD cognitive style make an uncompleted problem solving plan and use the formula of plane area related by given problems. (3) When implementing the problem solving plan, subjects with FI cognitive styles were ableto implement the plant completely, and able identify the logical reason. Subject with FD cognitive style were able to implement problem solvingas planned, but unable to givea logical reasonabout the results, evenless confident with his results. (4) Subjects with FI cognitive style were ableto checking back the answer by recalculate the result. Subjects check the answer by comparing the results obtained with the unit costper meter, orcal culate by reverse method. Subject with FD cognitive style was checking his answer by stare the result and unable to checking back the answer.